PHBS Tk Aisyiyah Bustanul Athfal 2 Grogol Jakarta Barat - Siti Mutyasari; Fadila Saskia; Mochamad Alfigo (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
Many diseases that occur are caused by poor living behavior of the community itself. This includes illnesses experienced by kindergarten students. At Asisyiyah Kindergarten Bustanul Athfal 2 Grogol Jakarta Barat, on average every week there are students who do not go to school because they are sick, Among others: diarrhea, cold cough, typhoid, etc. Observation results show that: students cannot wash yet hands properly, students are not used to washing their hands, there are no washing facilities in the classroom hands, students are accustomed to snacking carelessly in front of school, students do not throw rubbish in the trash, Many students have difficulty eating and more often snack on instant food at food stalls. Implementation method:promotive by providing education on clean and healthy living behavior to kindergarten students involving students and their parents, facilitate clean hand washing stations in each class, forming an alert group cleanliness in schools consisting of teachers, students and food sellers. Results of implementing activities among others students' knowledge and awareness about clean and healthy living behavior has increased, students have practicing clean hand washing before and after eating, the school's hygiene monitoring group is in place formed and functioning. Kindergarten students' clean and healthy living behavior includes: washing hands, throwing away rubbish in place, brushing your teeth, avoiding cigarette smoke, eating nutritious food, defecating and in the bathroom, cutting nails, brushing shoes, cleaning clothes. Conclusion: with implementation of community service by Universitas Muhammadiyah Jakarta lecturers at ABA 2 Grogol Jakarta Barat Kindergarten, then there is a change in the healthy clean behavior of ABA 2 Kindergarten students who were previously unhealthy to become healthy behavior